Incidencia de la parasitosis intestinal y su relación con el estado nutricional en niños escolares, en zona urbano marginal -2025 - Verduga Delgado, Angy Graciela; Garate Sánchez, Ariana Pamela (My University, 2025)
The present research aimed to determine the incidence of intestinal parasitosis and its relationship with the nutritional status of schoolchildren in the urban-marginal area of “Los Vergeles” during the months of April to July 2025. Methodology a cross-sectional, correlational, and observational study with a mixed approach was conducted. The population consisted of 50 schoolchildren from the “Enriqueta de Wind de Laniado” Educational Unit. For data collection, structured surveys were applied to the children's guardians, coproparasitological analysis was carried out through direct fresh observation using saline solution, and anthropometric evaluations were conducted, including measurements of weight and height. The data obtained were recorded on technical data sheets and processed using the statistical software Jamovi, complemented by Microsoft Excel. Body Mass Index (BMI) and Waist-to-Height Ratio (WHtR) were calculated to determine nutritional status. Results the findings showed that 52% of the children were underweight, 34% had a healthy weight, and 14% were obese. Regarding the presence of intestinal parasites, 68% tested positive, with Entamoeba histolytica (26%), Giardia lamblia (16%), and Enterobius vermicularis (10%) being the most prevalent. The chi-square test revealed a statistically significant association between parasitosis and underweight (p = 0.044). Conclusion the presence of intestinal parasites negatively affects children's nutritional status, reinforcing the need to implement deworming campaigns, health monitoring, and nutritional education within school institutions.
La presente investigación tuvo como objetivo determinar la incidencia de la parasitosis intestinal y su relación con el estado nutricional en niños escolares de la zona urbano marginal “Los Vergeles”, durante los meses de abril a julio de 2025. Metodología Se realizo un estudio de tipo transversal, correlacional y observacional, con enfoque mixto. La población estuvo conformada por 50 escolares de la Unidad Educativa “Enriqueta de Wind de Laniado”. Para la recolección de datos se aplicaron encuestas estructuradas a los representantes de cada escolar, análisis coproparasitario mediante observación directa en fresco con solución salina, y evaluaciones antropométricas que incluyeron mediciones de peso y estatura. Los datos obtenidos fueron registrados en fichas técnicas y procesados mediante el software estadístico Jamovi, complementado con Microsoft Excel. Se calculó el índice de masa corporal (IMC) y el índice cintura-talla (ICT) para determinar el estado nutricional. Los resultados evidenciaron que el 52 % de los niños presentaban bajo peso, el 34 % un peso saludable y el 14 % obesidad. En cuanto a la presencia de parásitos intestinales, el 68 % resultó positivo, siendo Entamoeba histolytica (26 %), Giardia lamblia (16 %) y Enterobius vermicularis (10 %) los más prevalentes. La prueba de chi-cuadrado mostró una asociación estadísticamente significativa entre la parasitosis y el bajo peso (p = 0,044). Conclusión La presencia de parásitos intestinales afecta de forma negativa el estado nutricional infantil, lo que refuerza la necesidad de implementar campañas de desparasitación, control sanitario y educación nutricional dentro de las instituciones escolares.
Keywords: PARASITOSIS INTESTINAL; ESTADO NUTRICIONAL; INDICE DE MASA CORPORAL; ESCOLARES